1991
DOI: 10.1111/j.1532-5415.1991.tb04042.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of Antibiotic Use in Aged Nursing Home Patients

Abstract: Antibiotics are frequently prescribed for aged nursing home patients, often in the absence of a physician's examination and other features commonly performed in evaluation of specific infectious diseases. More than one-fifth of antibiotics prescribed by presumed active infections were for two infections usually thought not to require antibiotic therapy, "viral" upper respiratory infection (13%) and asymptomatic bacteriuria (9%). To optimize antibiotic use in nursing homes, greater attention should be directed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
104
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 35 publications
6
104
0
Order By: Relevance
“…32 However, previous research has consistently documented that 25%-75% of antibiotic treatments in long-term care facilities are inappropriate. 4,5,55 CMAJ | JUNE 26, 2017 | VOLUME 189 | ISSUE 25 E859…”
Section: Limitationsmentioning
confidence: 99%
“…32 However, previous research has consistently documented that 25%-75% of antibiotic treatments in long-term care facilities are inappropriate. 4,5,55 CMAJ | JUNE 26, 2017 | VOLUME 189 | ISSUE 25 E859…”
Section: Limitationsmentioning
confidence: 99%
“…Antibiotic therapy prescribed to nursing home patients is often inappropriate or unjustified. [54][55][56] Patients who do not receive initial evaluation by a physician or nurse practitioner during an episode of pneumonia appear to be more likely to die or to require transfer to a hospital. 57 Nursing home patients are frequently transported to hospital emergency departments for therapy that could be administered in the nursing home.…”
Section: L I N I C a L P R E S E N T A T I O Nmentioning
confidence: 95%
“…Based on the recommendations of a panel of infectious disease specialists and geriatricians 54 and a review of the literature, 4 a minimal diagnostic evaluation of a patient suspected of having pneumonia consists of the following:…”
Section: L I N I C a L P R E S E N T A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…2 On the other hand, urinary tract infection (UTI) is the most common infection in the elderly and the most frequent indication for prescription of antibiotics, accounting for 36% of all antibiotics given in long-term-care facilities (LTCFs). 3 Nonetheless, the contribution of UTI to febrile morbidity in LTCFs is not clear. Previous studies showed that the positive predictive value of bacteriuria for febrile UTI was only 11% and that UTI contributes to less than 10% of the episodes with clinically significant fever in a population with high prevalence of bacteriuria.…”
mentioning
confidence: 99%